Wonderful and loved by all - Haag, Martina; Haag, Martina; Haag, Martina (S/S Fladen Film, 2007)
Bella is a self-declared actress but with a rather small list of achievements. She is pushing forty, constantly broke and has very little else to show for herself. Not much is going her way, so one day she decides to be a little creative in a CV she sends around, pretending she has developed acrobat skills. Good for her, Ingmar Bergman is precisely looking for a gymnast actress able to perform serious acrobatics for his new play. Bella gets the role of her life, but her small lies will lead to big consequences ... --